2002
DOI: 10.1128/aem.68.11.5698-5703.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Invasiveness of Different Pulsed-Field Gel Electrophoresis Types of Listeria monocytogenes

Abstract: The virulence of different pulsed-field gel electrophoresis (PFGE) types of Listeria monocytogenes was examined by monitoring their ability to invade Caco-2 cells. Strains belonging to seven different PFGE types originating from both foods and humans were included. No significant differences in invasiveness were detected between strains isolated from humans and those isolated from food. Strains belonging to PFGE type 1 expressed a significantly lower ability to invade cells compared to strains belonging to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
2
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 27 publications
5
25
2
5
Order By: Relevance
“…During our PFGE analyses, we did not observe subclustering of clinical (and possibly more virulent) or environmental isolates. This observation agrees with a previous report (22) demonstrating no association between various PFGE types of L. monocytogenes and the strains' virulence potential for Caco-2 tissue culture cells. On the other hand, MLST identified three subclusters (A1, B1, and B2 [ Fig.…”
Section: Discussionsupporting
confidence: 83%
“…During our PFGE analyses, we did not observe subclustering of clinical (and possibly more virulent) or environmental isolates. This observation agrees with a previous report (22) demonstrating no association between various PFGE types of L. monocytogenes and the strains' virulence potential for Caco-2 tissue culture cells. On the other hand, MLST identified three subclusters (A1, B1, and B2 [ Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to ribotypes DUP-1038B and DUP-1042B, which produced significantly larger plaques than other ribotypes, ribotype DUP-1053A was found to have lower infectivity than other ribotypes. These findings are consistent with studies on food and human isolates using chicken embryo and Caco-2 tissue culture infection assays, which also revealed that some subtypes were more virulent than others (19,26). The concept of strain-specific virulence characteristics is also supported by the observation that the correlation between the two measures of cytopathogenicity (plaque size and infectivity) differed among ribotypes.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have also shown that lineage I strains are more common among human listeriosis cases and outbreaks than among animal cases, while lineage III strains are significantly more common among animal listeriosis cases than among human cases (17). From a biological perspective, however, clear correlations between specific genetic types or clonal groups and virulence characteristics remain to be established (19,26,30,42).…”
mentioning
confidence: 98%
“…Determination of cell association and invasion of L. monocytogenes was performed as described by Larsen et al (32), with some modifications. Enterocyte-like Caco-2 cells obtained from the Deutsche Sammlung von Mikroorganismen und Zellkulturen (Braunschweig, Germany) were cultured in Eagle's minimal essential medium (MEM) enriched with Glutamax and HEPES (Invitrogen, Tåstrup, Denmark) and supplemented with 20% heat-inactivated (30 min at 56°C) fetal calf serum (Invitrogen), 0.1 mM nonessential amino acids (Invitrogen), and 0.5 ml of gentamicin (50 mg/ml) (Invitrogen) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%